WOMEN’S ACCESS TO CREDIT FACILITIES AND ITS IMPACT ON AGRICULTURAL PRODUCTIVITY AND LIVELIHOOD OF RURAL FARMERS IN OHIMINI LOCAL GOVERNMENT AREA, BENUE STATE, NIGERIA - Omale, P.I.; Ajeh, O.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed women’s access to credit facilities and its impact on agricultural production and livelihood of rural farmers in Gboko Local Government Area of Benue State. Multi stage sampling procedure was used to select 120 respondents in the study area. Primary data were collected through a structured questionnaire and analysed using both descriptive statistics, Logit regression, factor Analysis, Multiple Regression and Paired Sample t-Test. Results revealed the mean age of 41 years, married (65.8%), and moderately educated (46.7% had secondary education). Only 53.3% had extension contact in the last year, and 27.5% belonged to farmers’ organizations. The dominant sources of agricultural information were fellow farmers (71.7%), radio/TV (65.8%), and family/friends (58.3%). Logit regression results showed that interest rate, collateral requirement, repayment terms, accessibility, and creditworthiness significantly influenced women’s access to credit (p < 0.05). Factor analysis extracted three major constraint dimensions financial/institutional barriers, accessibility/documentation challenges, and administrative bottlenecks explaining 70.2% of total variance. Multiple regression revealed that limited access to credit significantly reduced agricultural productivity (F = 31.71, p < 0.001), while paired-sample t-tests showed marked improvements in farm output, income, and asset ownership after accessing credit (p < 0.01). The study concludes that although women in Gboko LGA are active in farming, their potential remains hindered by institutional and financial barriers that restrict access to affordable credit. Enhanced access to credit positively influences productivity and improves household welfare. It is therefore recommended that government and financial institutions adopt gender-responsive lending policies, reduce interest rates and collateral requirements, simplify documentation procedures, expand microfinance outreach, and promote cooperative-based and digital credit delivery systems. These measures would strengthen women’s participation in agricultural development and contribute to rural poverty reduction.